Evolution of the Russian citation index as science sociology context - Borodin A. V. (Education and science in the modern context, 2018)
An area of research in the present article is process of obtaining new scientific knowledge in the Russian Federation. The factor of influence of institutes of a citation index on efficiency of scientific and technical progress acts as an object of a research. The main results of the conducted research are the sentences on saving of level of motivation of all categories of researchers consisting in implementation of full indexation of content of a scientific digital library of eLIBRARY.RU taking into account the available stratification, but, at least, with saving of full statistics of citings for the lower stratum now excluded.
Keywords: отношения; онтология; научно-технический прогресс; имитационное моделирование; индекс цитирования; citation index; институциональная ловушка; ontology; IDEF5; IDEF5; simulation modeling; наукометрия; institutional trap; положительная обратная связь; positive feedback; progress; QWERTY-эффект; scientometrics; relations; economics of QWERTY